(untitled) (Journal of Politics and International Studies, 2025)
The Pashtun National Jirga has emerged as a critical institution for restoring social order in the Pashtun belt. This paper examines the speeches of the Pashtun Tahafuz Movement (PTM) leadership, particularly those of Manzoor Pashteen, at the Pashtun National Jirga in October 2024, through a qualitative content analysis. This paper adopts Framing theory to analyse how PTM leadership has diagnosed socio-economic and political grievances, proposed effective solutions, and motivated a collective resistance. The findings through frames not only identified systematic marginalisation, historical trauma, and state negligence in the speeches of the PTM leader but also called for the strengthening of indigenous institutions like Jirga, demilitarisation, economic justice, and legal reforms.